Odpowiedzi

2010-03-30T20:09:49+02:00
A) =-3/4 -3/2+1=-5/4
b) =8 - 1/25 +2 +10= 19 24/25
c) -3*1= -3
  • Użytkownik Zadane
2010-03-30T20:13:58+02:00
A) -3a²+3a+1 dla a = -½
-3(-0,5)kwadrat+3*(-1/2)+1=
-3*1/4-3/2+1=
-0,75-1,5+1=
-1,25

b)-x³-y²-5z+10 dla x =-2 , y=-1/5,z=-2
(-2)do szscianu-(-1)kwadrat-5*(-2)=-8-1+10+10=11

c)(x +2/x)*(-2/x-x²) dla x= -1
[-1+(2/-1)]*[-2/-1-(-1)kwadrat=
(-1-2)*(2-1)=-2+1-4+2=-3
Najlepsza Odpowiedź!
2010-03-30T20:32:04+02:00
Oblicz wartości liczbowe wyrażeń
a) -3a²+3a+1 dla a = -½
-3*(-1/2)²+3(-1/2)+1 =
-3*1/4-3/2+1 =
-3/4-3/2+1 =
-9/4+1 = -5/4

b)-x³-y²-5z+10 dla x =-2 , y=-1/5,z=-2/5
-(-2)³-(-1/5)²-5(-2/5)+10 =
8-1/25+2+10 =
7,96+12 = 19,96

c)(x +2/x)*(-2/x-x²) dla x= -1
(-1+2/-1)*(-2/-1-(-1)² =
(-1-2)*(2-1) =
-3*1 = -3